Third Wave Feminisim in Star's Emily in Paris - Yusi Maryuningsih; Ririn Trisnawati; Mia Fitria Agustina (English Literature Studi Program Universitas Islam Makassar, 2023)
Emily in Paris, directed by Darren Star, tells the story of a woman who recently moved from America to Paris to replace and take over the responsibility of her boss who can't go on a business trip in a year. In this paper, the authors want to prove the existence of the wave 3 feminism movement in the film Emily In Paris. This study used descriptive qualitative method and researchers used note-taking as a tool. Data analysis refers to the steps involved in analyzing data to answer a research problem. The data are in the form of characters and characterization, dialogues, descriptions, plot, scenes or events in the film Emily In Paris. And for the final result, we found that the third wave of feminism is reflected in Emily’s character which has the different point of view with the sexist. And then Emily also embraced woman empowerment in the life of Emily Cooper.